Türkiye'nin dış borçları ve ekonomik etkileri - Demiroğulları, Meserret (Anadolu Üniversitesi, 1989)
The external debt is one of the most important problems in developing countries and needs to solve. In Turkey and all other developing countries, it is needed external resources to finance necessary investments and so to reach the expected growth rate. Because the external deficit, which occurs because of the lack of internal savings and being the import expanditures are greater than the export incomes, prevents growing these countries. It's known that the external debts of Turkey reached to very high levele and the external debt payments were done by new external debts in 1963-1987 period. At the end of 1987, total amount of the external debts used, was 38.304 billion S. In 1987 the external debts portion in GNP reached to % 60 and the amount of the external debts increased four times more than the export incomes. To be useful the external debts for the economy of Turkey these debts should be used not for current consumptions but to finance the projects which expand the production capacity thus increase the export.
Sadece dijital ortamda erişilebilir.
Keywords: Dış borçlar